An institutional assessment of UISC (Union Information and Services Center) : a case study of two selected Union Parishad of Bangladesh - Rahman, Md. Oliur (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.